Implementation Of Fulfillment Of Workers' Wage Rights With A Particular Time Working Agreement System At Pt.X - Adila Azani; Siti Hajaiti Hoesin (Faculty of Law, University of Mataram, 2022)
Legal regulations regarding wages should be the basis for employers/entrepreneurs to implement provisions regarding the fulfillment of wage rights for workers. However, the problems that often occur in the field are fulfillment of wage rights by employers to workers who are not subject to these legal provisions. One of the facts that happened to PT. X has 150 employees under the PKWT system and all of these workers receive wages below the minimum wage stipulated by the government in the current year.This is of course contrary to the provisions of labor law in the field of wages, in particular the provisions of Article 90 paragraph (1) of the Manpower Law. Based on the description of the background, the problems studied in this study are: 1. How is the implementation of the fulfillment of workers' wage rights with a certain time work agreement system at PT. X?. 2. How is the implementation of local labor inspection in fulfilling workers' wage rights with a certain time work agreement system at PT. X?. This study uses a juridical-sociological approach and descriptive research, interview data collection techniques and document studies. Based on the research conducted, the results obtained are: 1. Implementation of the fulfillment of workers' wage rights at PT. X has not been implemented as the legal provisions in the field of employment, there are 4 main legal problems that occur, namely the payment of wages below the minimum wage, payment of wages is often late than the agreed time between workers and PT. X, payment of wages for sick workers and components of wages that are not in accordance with legal provisions. 2. The implementation of labor inspection has not been implemented properly in enforcing labor norms at PT. X especially in terms of fulfilling workers' wage rights.